Protein refractive index increment is determined by conformation as well as composition. (4th October 2018) - Khago, Domarin; Bierma, Jan C; Roskamp, Kyle W; Kozlyuk, Natalia; Martin, Rachel W
Abstract: The refractive index gradient of the eye lens is controlled by the concentration and distribution of its component crystallin proteins, which are highly enriched in polarizable amino acids. The current understanding of the refractive index increment ( ) of proteins is described using an additive model wherein the refractivity and specific volume of each amino acid type contributes according to abundance in the primary sequence. Here we present experimental measurements of for crystallins from the human lens and those of aquatic animals under uniform solvent conditions. In all cases, the measured values are much higher than those predicted from primary sequence alone, suggesting that structural factors also contribute to protein refractive index.